Hydroxyurea compared with anagrelide in high-risk essential thrombocythemia. - Harrison, C; Campbell, P; Buck, G; Wheatley, K; East, C; Bareford, D; Wilkins, B; van der Walt, JD; Reilly, J; Grigg, A; Revell, P; Woodcock, B; et al. (2005)
BACKGROUND: We conducted a randomized comparison of hydroxyurea with anagrelide in the treatment of essential thrombocythemia. METHODS: A total of 809 patients with essential thrombocythemia who were at high risk for vascular events received low-dose aspirin plus either anagrelide or hydroxyurea. The composite primary end point was the actuarial risk of arterial thrombosis (myocardial infarction, unstable angina, cerebrovascular accident, transient ischemic attack, or peripheral arterial thrombosis), venous thrombosis (deep-vein thrombosis, splanchnic-vein thrombosis, or pulmonary embolism), serious hemorrhage, or death from thrombotic or hemorrhagic causes. RESULTS: After a median follow-up of 39 months, patients in the anagrelide group were significantly more likely than those in the hydroxyurea group to have reached the primary end point (odds ratio, 1.57; 95 percent confidence interval, 1.04 to 2.37; P=0.03). As compared with hydroxyurea plus aspirin, anagrelide plus aspirin was associated with increased rates of arterial thrombosis (P=0.004), serious hemorrhage (P=0.008), and transformation to myelofibrosis (P=0.01) but with a decreased rate of venous thromboembolism (P=0.006). Patients receiving anagrelide were more likely to withdraw from their assigned treatment (P<0.001). Equivalent long-term control of the platelet count was achieved in both groups. CONCLUSIONS: Hydroxyurea plus low-dose aspirin is superior to anagrelide plus low-dose aspirin for patients with essential thrombocythemia at high risk for vascular events.